Zoning System Analysis in New Student Admissions Based on the Availability of School Facilities in Bekasi City - Adrian; Sony Nugratama Hijrawadi; Syahrul Ramadhan; Yustika Amalia Rohmah (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2020)
This research was conducted to determine the availability of state junior high schools (SMP) and state senior high schools (SMA) based on the school zoning system. So that the ideal number of junior and senior high schools in each district will be obtained. To achieve the research objectives using the carrying capacity formula of service facilities. The results of this study indicate the calculation of carrying capacity obtained a value of> 1, which means that the sub-district has been able to meet the needs of the population for public high school facilities. Meanwhile, the sub-districts that have fulfilled the carrying capacity of the facilities of State Junior High Schools with a carrying capacity of> 1 are Jatiasih and East Bekasi districts, which means that these districts can meet the needs of educational service facilities. The Bekasi Selatan sub-district received a score equal to 1, which means that it is balanced between the service needs and the available educational facilities (SMPN). Whereas in the application of the zoning system for the New Student Admissions in Bekasi City, for the State Senior High School level with an area of ​​7 Km from schools and State Junior High Schools, it can reach 1 Km from the school.